A rapid stabilization method of the flexible inverted pendulum based on constrained boundary circumferential motion. (15th March 2023) - Chu, Wei; Li, Chaofeng; Zhou, Yang
Highlights: A new method to control the circumferential motion of the boundary is proposed. The theory of suppression is derived from dynamic analysis. An experiment platform corresponding to the theoretical model is built. The control parameters are optimized by simulation and experimental results. Abstract: This paper proposed a method to control the circumferential motion of the constraint boundary of the flexible inverted pendulum to achieve its fast stability. Firstly, the dynamic equation of the system is obtained by the beam theory. The displacement of the flexible inverted pendulum is used as the input to explore the relationship between the output of the constrained boundary and the displacement. The phase delay control method is used to control the circumferential displacement. Then, the influence of the control parameters delay time and motion range on the suppression efficiency is obtained through the damping analysis. The same results as the theory are obtained through simulation. Finally, the corresponding experimental platform is built. The experimental results show that the method can effectively suppress the vibration of the flexible inverted pendulum.